Improving Bank management Under Macro economic Context - Case of ACB Bank in Vietnam - VU, NGUYEN THANH; HUY, DINH TRAN NGOC; NHAN, VO KIM; DUNG, NGUYEN VIET; TAM, BUI QUANG; DUC, PHAN MINH; DAT, NGUYEN VAN; HUNG, NGUYEN THANH (The journal of contemporary issues in business and government, 2021)
Vietnam experienced the year 2015 with low CPI as of 0.6%. It is the time to suggest solutions to improve bank management and leadership in the country in a changing macro economic context. This paper evaluate bank risks in famous risk model under impacts of both macro internal and external variables during 2 special periods: pre-Low (L) inflation time 2011- 2015and post-L time 2015-2020 in the country. Therefore, in our paper, we aims to measure and evaluate how much effects in the market risk of one of big listed Vietnam commercial bank, Asia Commercial Bank (ACB) during the 2 special periods with semiannual data. We use synthesis statistics methods, and dialectical materialism method, combined with econometric model with 9 macro variables, and figure out that lending rate and risk free rate has positive impacts with bank risk. It implies that increase in lending rate, together with decrease in Rf will increase market risk. Then, we will suggest recommendations for improving bank management capabilities and relevant government agencies. Our recommendation can be used for reference in many other developing markets. JEL classification numbers: M21, G12, G30, E58, E62